2010
DOI: 10.3892/ijmm_00000486
|View full text |Cite
|
Sign up to set email alerts
|

UVB radiation induces an increase in intracellular zinc in human epidermal keratinocytes

Abstract: Abstract. Ultraviolet (UV) radiation is known to cause oxidative stress, inflammation, DNA damage and apoptotic cell death; however, many details of these malign mechanism have yet to be elucidated. In this study, the exposure of adult human epidermal keratinocytes (HEKa) with UVB (>100 mJ/ cm 2 ) resulted in the significant increase of intracellular zinc that was released from its storage and was detected by fluorescent zinc indicators. Toxicity testing revealed that UVB-induced zinc release in HEKa is associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Preparation and generation of FAM172A recombinant protein was previously described ( 2 ). Then protein was boiled with 5X SDS gel loading buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation and generation of FAM172A recombinant protein was previously described ( 2 ). Then protein was boiled with 5X SDS gel loading buffer.…”
Section: Methodsmentioning
confidence: 99%
“…FAM172A was first identified in human aortic endothelial cells, THP-1-derived macrophages, and human aortic smooth muscle cells at the translation level through western blotting ( 2 , 3 ). Feng et al found that FAM172A was notably downregulated among hepatocellular carcinoma or cirrhotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The highest individual fold change in this group was observed for FAM172A . which remains a poorly characterized gene [ 75 - 77 ] The CCNYL1 gene is more informative, with the second highest fold downregulation in BORIS KD and BORIS binding in its promoter. It is a CDK6 cyclin, which is normally specific for germ cells [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The retroviral infection of HPV16 E6/E7 genes was performed on HFKs. 46 By following a reported method, 47 human Tcf7l1 cDNA was subcloned into a pDC315 vector (gifted by Dr. Cheng Pan, Wuhan University) and then transfected into HFKs. Using gene-specific PCR primers ( Supplementary Table S2 ), Tcf7l1 cDNA was incorporated with sequences of Eco RI and Nhe I, and then ligated into the corresponding restriction enzyme sites in vector.…”
Section: Methodsmentioning
confidence: 99%